The temperature coefficient of the optical path length as a function of the temperature in different optical glasses - Steimacher, A.; Medina, A. N.; Bento, A. C.; Rohling, J. H.; Baesso, M. L.; Reynoso, VCS; Lima, S. M.; Petrovich, M. N.; Hewak, D. W. (Elsevier B.V., 2004)
An interferometric technique was used to determine the temperature coefficient of the optical path length (dS/dT) as a function of the temperature in several optical glasses. The temperature range was between 25degreesC and 180degreesC. The studied samples included undoped and doped oxide glasses, such as low silica calcium aluminosilicate, phosphates, borates and also chalcogenides. The oxide glasses had dS/dT between 10 X 10(-6) K-1 and 20x10(-6) K-1, while for the chalcogenides, these were around 70 x 10(-6)K(-1). The results showed that dS/dTs increased with the temperature in all samples. For samples doped with Nd the dS/dT values were found to be independent of concentration. on the other hand, for the phosphate glass doped with Cr, dS/dT increased about 5% when compared with the Nd doped one. In conclusion, the used interferometric method, which is a considerably simpler and a lower cost technique, and is a useful tool to measure dS/dT in semi-transparent glasses as a function of the composition and temperature. (C) 2004 Elsevier B.V. All rights reserved.